A Decision support system to hit target sample distribution quota and consumers on outdoor product sampling - Tumamao, Mary Grace
The research was conducted to address the problem of not hitting the target consumers and number of distribution samples on outdoor locations. Giving free samples on indoor locations has been long practiced and is proven strategy to increase sales or attract customers for newly launched products or variant. However, the success of sampling on outdoor locations is still questionable due to uncontrolled environment. Excess product samples and not distributing to target consumers are just added costs for the company. The research then arms to produce a tactical solution, by means of creating a decision support system that will aid in finding locations where target market of the product are located and where the distribution of samples will be maximized. The decision support system presented gets information from data sources such as user input, government website and company ERP and marketing databases. These data are then consolidated into a data warehouse for AHP-GP modelling and subsequently produce results with less deviation from the defined objectives of the study. The research also introduces the use of two-stage analysis of success factors to consider, not only the major factors such as demographics, but also minor factors such as proximity of locations to crowded areas, supply and location accessibility.